Principles of Economics, Brief Edition (The Mcgraw-Hill Series Economics) - Frank Robert H (Mc Graw Hill Higher Education, 2010)
n recent years, innovative texts in mathematics, science, foreign languages, and other fields have achieved dramatic pedagogical gains by abandoning the traditional encyclopedic approach in favor of teaching a shorter list of core principles in depth. Two well-respected writers and researchers, Bob Frank and Ben Bernanke, have shown that the less-is-more approach affords similar gains in introductory economics. The authors introduce a coherent short list of core principles and reinforce them by illustrating and applying each in numerous contexts. Students are periodically asked to apply these principles and to answer related questions and exercises. The BRIEF editions were developed for instructors who appreciate core principles approach, and desire a more manageable amount of content and slightly less rigor. In the brief editions, the authors made careful choices of material to eliminate and condense, in order to produce of more concise coverage.